Polycyclic aromatic hydrocarbons (PAHs) in Greater Cairo water supply systems - Mahmoud M. Fouad; Ahmed S. El-Gendy; Mostafa M. H. Khalil; Taha M. A. Razek (Journal of Water and Health, 2022)
Polycyclic aromatic hydrocarbons (PAHs) pose a constant threat to the environment and public health. There are numerous activities in the Greater Cairo area that emit and release significant amounts of PAHs. Concentrations of these PAHs are released into the air and mixed with surface water, limiting its use. In this study, 17 PAH compounds are mapped at eight sites along the Nile River and its tributaries in Greater Cairo. In addition, their removal efficiency is evaluated with the conventional treatment in eight water treatment plants. PAHs were analyzed using GC–MS from January to December 2018. Naphthalene, anthracene, fluorene, pyrene, and phenanthrene were detected. The total amount of PAHs in raw water was highest in Shamal Helwan (1,325 ± 631 ng/l) and lowest in Mostorod (468 ± 329 ng/l), and the removal ranged from 25 to 31%. Further research is needed to integrate other techniques to reduce PAHs using the conventional treatment, and more efforts should be made to reduce the presence and release of PAHs in raw water. HIGHLIGHTS All detected PAHs correlate with each other and are of similar origin.; Pulsator clarifiers were more effective than recirculating sludge in the reduction of PAH.; The maximum rate of PAH removal by the conventional treatment was 31% in the study.; Source prevention and additional treatment are required for effective PAH reduction.;